Prevalence of Balantidium coli in Buffaloes at different areas of Mymensingh (Journal of the Bangladesh Agricultural University, 2011)
Balantidium coli is a common protozoan disease of animals. A total of 151 buffaloes were examined through faecal examination, of which 68 (45.03%) found to be infected with B. coli infection. Prevalence of B. coli infection was relatively higher in adult buffaloes (49.52%) aged > 5 years than young (39.29%) aged > 2- ≤ 5 years and buffalo calves (27.78%) aged ≤ 2 years. Higher prevalence of B. coli was observed in female (47.32%) than that of male (38.46%) buffaloes which are not statistically significant. Prevalence of B. coli infection was significantly (p